2000
DOI: 10.1364/josaa.17.001697
|View full text |Cite
|
Sign up to set email alerts
|

Optical aberrations of the human cornea as a function of age

Abstract: We investigated how the optical aberrations associated with the anterior surface of the human cornea change with age in a normal population. Aberrations were computed for a central part of the cornea (4, 5, and 6 mm in diameter) from the elevation data provided by a videokeratographic system. Measurements were obtained in 59 normal healthy, near-emmetropic [spherical equivalent lower than 2 diopters (D)] subjects of three age ranges: younger (20-30 years old), middle-aged (40-50 years old), and older (60-70 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
1
12

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(165 citation statements)
references
References 13 publications
7
145
1
12
Order By: Relevance
“…[12][13][14] This latter scenario was included in order to estimate the performance of the IOL once it is implanted in the aphakic eye. Figures 3 and 4 show the MTF curves and the PSF, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] This latter scenario was included in order to estimate the performance of the IOL once it is implanted in the aphakic eye. Figures 3 and 4 show the MTF curves and the PSF, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that corneal HOAs remain rather stable with age. [12][13][14] From those studies, an average corneal pattern could be obtained. To combine (add) this average corneal pattern with each IOL's pattern we used the abovementioned custom-made MATLAB-based application.…”
Section: Image Quality Parametersmentioning
confidence: 99%
“…35,[37][38][39][40][41][42] With increasing age, a general shift in the axis of astigmatism is found from a predominance of WTR astigmatism (in adults younger than 40 years) to a predominance of ATR astigmatism (in adults older than 40 years). 35,[38][39][40]42,43 This shift in astigmatic axis in older age appears to be due to changes in corneal curvature. [38][39][40]42 In a cross-sectional study of corneal and total astigmatism, Anstice 38 found that internal astigmatism remained relatively stable over time and that changes in astigmatism throughout life were due primarily to changes in corneal curvature.…”
Section: Astigmatism In Adultsmentioning
confidence: 99%
“…[1][2][3] However, spherical aberration of the crystalline lens increases with age, 4 whereas the corneal aberration changes little throughout life. 5,6 Therefore, the total ocular aberration increases with age, leading to deterioration of optical quality in older subjects. [7][8][9][10] When the crystalline lens is replaced by an intraocular lens (IOL) in cataract surgery, further changes may occur.…”
Section: Introductionmentioning
confidence: 99%